Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 154621 by liberty last updated on 20/Sep/21

 ∫ ((√(x^2 +x+1))/(x^2 +x)) dx

x2+x+1x2+xdx

Commented by mathdanisur last updated on 20/Sep/21

=∫ (dx/( (√(x^2 +x+1))))_()  +∫(dx/((x^2 +x)(√(x^2 +x+1))))_()   (1) ⇒ ln∣x+(1/2)+(√(x^2 +x+1))∣  and  (2) ⇒ ln∣((2x^2 +2x-1+(2x+1)(√(x^2 +x+1)))/(2x^2 +2x+1+(2x+1)(√(x^2 +x+1))))∣  say → s=x+(√(x^2 +x+1)) ⇒ dx=((2(s^2 +s+1))/((2s+1)^2 ))ds  ... ⇒ =ln∣((2x^2 +2x-1+(2x+1)(√(x^2 +x+1)))/(2x^2 +2x+1+(2x+1)(√(x^2 +x+1))))∣+C

=dxx2+x+1+dx(x2+x)x2+x+1(1)lnx+12+x2+x+1and(2)ln2x2+2x1+(2x+1)x2+x+12x2+2x+1+(2x+1)x2+x+1says=x+x2+x+1dx=2(s2+s+1)(2s+1)2ds...=ln2x2+2x1+(2x+1)x2+x+12x2+2x+1+(2x+1)x2+x+1+C

Answered by ARUNG_Brandon_MBU last updated on 20/Sep/21

I=∫((√(x^2 +x+1))/(x^2 +x))dx=∫((x^2 +x+1)/((x^2 +x)(√(x^2 +x+1))))dx    =∫(dx/( (√(x^2 +x+1))))+∫(dx/((x^2 +x)(√(x^2 +x+1))))    =∫(dx/( (√((x+(1/2))^2 +(3/4)))))+∫((1/x)−(1/(x+1)))(dx/( (√(x^2 +x+1))))    =argsinh(((2x+1)/( (√3))))+∫(dx/(x(√(x^2 +x+1))))−∫(dx/((x+1)(√(x^2 +x+1))))    =ln∣(((2x+1)/( (√3))))+(√(1+(((2x+1)/( (√3))))^2 ))∣−∫((udu)/( u^2 (√((1/u^2 )+(1/u)+1))))                                +∫((vdv)/( v^2 (√(((1/v)−1)^2 +((1/v)−1)+1))))   { ((u=(1/x))),((v=(1/(x+1)))) :}⇒ { ((du=−(dx/x^2 ))),((dv=−(dx/((x+1)^2 )))) :}⇒ { ((−(1/u^2 )du=dx)),((−(1/v^2 )dv=dx)) :}  I=ln∣(((2x+1)/( (√3))))+(√(1+(((2x+1)/( (√3))))^2 ))∣−sgn(u)∫(du/( (√(u^2 +u+1))))+sgn(v)∫(dv/( (√(v^2 −v+1))))    =ln∣(((2x+1)/( (√3))))+(√(1+(((2x+1)/( (√3))))^2 ))∣−sgn(u)ln∣(((2u+1)/( (√3))))+(√(1+(((2u+1)/( (√3))))^2 ))∣                    +sgn(v)ln∣(((2v−1)/( (√3))))+(√(1+(((2v−1)/( (√3))))^2 ))∣+C

I=x2+x+1x2+xdx=x2+x+1(x2+x)x2+x+1dx=dxx2+x+1+dx(x2+x)x2+x+1=dx(x+12)2+34+(1x1x+1)dxx2+x+1=argsinh(2x+13)+dxxx2+x+1dx(x+1)x2+x+1=ln(2x+13)+1+(2x+13)2uduu21u2+1u+1+vdvv2(1v1)2+(1v1)+1{u=1xv=1x+1{du=dxx2dv=dx(x+1)2{1u2du=dx1v2dv=dxI=ln(2x+13)+1+(2x+13)2sgn(u)duu2+u+1+sgn(v)dvv2v+1=ln(2x+13)+1+(2x+13)2sgn(u)ln(2u+13)+1+(2u+13)2+sgn(v)ln(2v13)+1+(2v13)2+C

Answered by EDWIN88 last updated on 20/Sep/21

I=∫(((√(x^2 +x+1))+1−1)/((x^2 +x+1)−1)) dx  I=∫ (((√(x^2 +x+1))−1)/(((√(x^2 +x+1))−1).((√(x^2 +x+1))+1)))dx   + ∫(dx/(x^2 +x))  I_1 =∫ (dx/( (√(x^2 +x+1))+1)) =∫ (dx/( (√((x+(1/2))^2 +(3/4)))+1))  set x+(1/2)=((√3)/2)tan α   I_1 =∫ ((sec^2 α(sec α−1))/((sec α+1)(sec α−1))) dα  I_1 =∫ ((sec^3 α−sec^2 α)/(tan^2 α)) dα  I_1 =ln (sec (tan^(−1) ((2/( (√3)))x+(1/( (√3)))))+(2/( (√3)))x+(1/( (√3))))−         (1/(sin (tan^(−1) ((2/( (√3)))x+(1/( (√3)))))))−(1/(((2/( (√3)))x+(1/( (√3))))))+c_1   I_2 = ∫ (dx/(x^2 +x))=∫ (dx/(x(x+1)))=∫ ((1/x)−(1/(x+1)))dx  I_2 =ln x−ln (x+1)+c_2   ∴ I=I_1 +I_2

I=x2+x+1+11(x2+x+1)1dxI=x2+x+11(x2+x+11).(x2+x+1+1)dx+dxx2+xI1=dxx2+x+1+1=dx(x+12)2+34+1setx+12=32tanαI1=sec2α(secα1)(secα+1)(secα1)dαI1=sec3αsec2αtan2αdαI1=ln(sec(tan1(23x+13))+23x+13)1sin(tan1(23x+13))1(23x+13)+c1I2=dxx2+x=dxx(x+1)=(1x1x+1)dxI2=lnxln(x+1)+c2I=I1+I2

Terms of Service

Privacy Policy

Contact: info@tinkutara.com